Risk-reducing salpingectomy: considerations from an OBGYN perspective - Alexandra Lukey; A. Fuchsia Howard; Alice J. Mei; Michael R. Law; David Huntsman; Celeste Leigh Pearce; Rafael Meza; Gillian E. Hanley (BMC Cancer)
Abstract Background With recent evidence that opportunistic salpingectomy is effective in preventing high grade serous carcinoma, it is imperative to consider the optimal use of this procedure. In this research, we investigated the opinions of obstetrician-gynecologists (OBGYNS) about the acceptability of using salpingectomy as a stand-alone surgery for people at higher-than-average lifetime risk (but without a pathogenic variant that increases risk for ovarian cancer) known as ‘risk-reducing salpingectomy’(RRS). Methods We conducted semi-structured interviews with purposefully sampled practicing OBGYNs in the province of British Columbia, Canada. We used qualitative interpretive description with inductive thematic analysis for data analysis. Our work was informed by the theoretical framework of acceptability. Results The nineteen participants included physicians from both general obstetrics and gynecology practices, as well as subspecialties. OBGYNs generally found RRS to be acceptable, though this acceptability was conditional on clinical, patient, and system-level factors. Five major themes suggest that: (1) There are risks and benefits of RRS, that if balanced might support acceptability; (2) It is important to define and identify the correct patient for RRS; (3) OBGYNs value patient autonomy in the decision to undergo RRS; (4) Reproductive justice and equity are intertwined and influenced by the history of forced and coerced sterilization; and (5) Formal guidance and the right environment are enablers of RRS. Conclusions This work provides initial evidence that, from the OBGYN perspective, RRS is acceptable in the right patient population, with considerations from those practicing on the front lines of ovarian cancer prevention.